Touching the future of training: investigating tangible interaction in virtual reality - Rettinger, Maximilian; Rigoll, Gerhard (Frontiers in Virtual Reality, 2023)
Virtual reality offers exciting new opportunities for training. This inspires more and more training fields to move from the real world to virtual reality, but some modalities are lost in this transition. In the real world, participants can physically interact with the training material; virtual reality offers several interaction possibilities, but do these affect the training's success, and if yes, how? To find out how interaction methods influence the learning outcome, we evaluate the following four methods based on ordnance disposal training for civilians: 1) Real-World, 2) Controller-VR, 3) Free-Hand-VR, and 4) Tangible-VR in a between-subjects experiment (n = 100). We show that the Free-Hand-VR method lacks haptic realism and has the worst training outcome. Training with haptic feedback, e.g., Controller-VR, Tangible-VR, and Real-World, lead to a better overall learning effect and matches the participant's self-assessment. Overall, the results indicate that free-hand interaction is improved by the extension of a tracked tangible object, but the controller-based interaction is most suitable for VR training.